1989
DOI: 10.1139/m89-060
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in putrefactive anaerobe 3679 (Clostridium sporogenes) induced by sorbate, hydrochloric acid, and nitrite

Abstract: Putrefactive anaerobe 3679 (Clostridium sporogenes), a gram-positive bacterium, was examined by light and electron microscopy during normal growth and in a medium containing sorbate (50 mM, pH 6.5), hydrochloric acid (pH of medium adjusted from 7 to 5 with HCl), or nitrite (1 mM, pH 7). During the early exponential growth phase, untreated cells were filamentous and nonseptate, but became septate later and divided when the culture entered the stationary phase. Untreated short and filamentous cells had a double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In our work we found a reduction of ≥6 logs CFU/ml of C. sporogenes concluding that the mode of action involved damaging inner and outer bacterial membranes resulting in necrosis thereby killing E. coli O157: H7 [42]. A similar result was found in the work of Ronning and Frank (1989) where they microscopically observed the growth phases of C. sporogenes injured by sorbate, hydrochloric acid and nitrite in the medium [43]. Inhibitory action of sorbate and hydrochloric acid was found similar; the cells were with distorted shapes M A N U S C R I P T…”
Section: A N U S C R I P Tsupporting
confidence: 88%
See 1 more Smart Citation
“…In our work we found a reduction of ≥6 logs CFU/ml of C. sporogenes concluding that the mode of action involved damaging inner and outer bacterial membranes resulting in necrosis thereby killing E. coli O157: H7 [42]. A similar result was found in the work of Ronning and Frank (1989) where they microscopically observed the growth phases of C. sporogenes injured by sorbate, hydrochloric acid and nitrite in the medium [43]. Inhibitory action of sorbate and hydrochloric acid was found similar; the cells were with distorted shapes M A N U S C R I P T…”
Section: A N U S C R I P Tsupporting
confidence: 88%
“…Furthermore, cell wall appeared to be thickened and the outer wall was absent in many areas [43]. Marais and Brozel (2006) concluded that different reactive chemical species (e.g.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%